TINDAK PIDANA KEKERASAN SEKSUAL DALAM RUMAH TANGGA DALAM UU No.23 TAHUN 2004 TENTANG PKDRT - Sholihati, Wildya Laila; Anwar, Syahrul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the criminal act of sexual violence within the household as regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law). Sexual violence constitutes a violation of human rights that frequently occurs in domestic spaces and reflects an unequal power relation between perpetrator and victim. This research applies a normative juridical method with conceptual and statutory approaches. The findings reveal that sexual violence in the household is not limited to forced sexual intercourse but also includes coercion of deviant sexual practices and forced sexual relations with third parties. The PKDRT Law explicitly prohibits sexual violence under Article 5(c) and Article 8, and stipulates criminal sanctions under Articles 46–48, with penalties ranging up to 20 years imprisonment or fines of up to IDR 500,000,000. However, the study identifies inconsistencies in sanction provisions, particularly regarding minimum and maximum penalties. The research underscores the need for consistent law enforcement, gender-sensitive perspectives, and victim-centered approaches to ensure that the objectives of the PKDRT Law providing protection and preserving family integrity can be fully realized.